Legal identity as a socio-cultural phenomenon and its significance for legal development - Bratasiuk, Maria; Parashchuk, Lilia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article highlights the problem of legal identity and its role in legal development. The need for intensive formation of legal identity among citizens of modern Ukraine as a factor of Ukrainian legal development and legal European integration is emphasized. Legal identity expresses the identity of an individual and his/her self-awareness, self-awareness in law. It is an integral feature of personality, a condition for its formation. It is not a substance, it is a process, it is asserted as an interaction of identifications, the result of which is the individual's awareness of personal qualities, codes and stereotypes of thinking, ways of behaving. Identity is the duty of every person, a part of his personal being, which helps him/her to feel himself / herself  as a person, to realize his/her own dignity.A person identified in the legal sense asserts himself / herself as a real subject of law, has a developed sense of human dignity, is aware of his/her personal qualities as a subject of law, learns methods of legal behavior, feels his/her  belonging to the legal community, his / her people, accepts the legal culture, the paradigm of national rights, etc. Particularly significant in legal identification is the ability of an individual to realize his/her inalienable natural rights, create, develop law, be responsible for its implementation, and protect it.    Legal identity implies a constant interaction between the integrity of our existence and the integrity of the legal sphere with its entire spectrum of conditions that surround us. It promotes a sense of predictability, the ability to predict aspects of legal life, events and patterns of behavior. If the integrity of the legal reality is violated, the legal identity will be far from complete, torn and unsettled, blurred.The faster a person's national identity is formed, the faster the legal identity will be formed, although this interdependence is not automatic. People without a formed national legal identity feel indifferent about human rights, the problem of legal justice, etc. If there are many such people in the country, the problem of injustice in various forms will not have a basis for solution. Because it is the mature, really formed subjects of law, who have developed as people of the national type and citizens, who are responsible for the fate of national law, legal development, human rights, the rule of law, etc.